Philippine folk dances - Aquino, Francisca Reyes (Manila, Philippines : [publisher not identified], 1960)
During the past few years, marked interest in folk dances has been manifested throughout the country.
Binasuan -- Bucasoy -- Imunan -- Jota Cagayana, La -- Kalapati -- Katlo -- Kin-naras -- Kuradang -- Kuratsa boholana -- Lanceros de negros -- Lauderes -- Lerion -- Pateado -- Rigodon de Honor -- Sapatya -- Sayaw ed tapew na bangko -- Sayaw santa isabel -- Sayaw sa palaton -- Sinurog -- Soryano -- Tinikling ha bayo -- Urukay -- Index.
Includes index.
Keywords: FOLK DANCE -- PHILIPPINES